Algunhas observacións sobre a Gramática elemental del gallego común de Ricardo Carvalho Calero - Sánchez Rei, Xosé Manuel (Madrygal. Revista de Estudios Gallegos, 2008)
This article contains a series of reflections concerning the characteristics and enormous importance which, at a particular time, was held by the Gramática elemental del gallego común, by Ricardo Carvalho Calero, a work which was greatly influential in spreading the Galician language throughout the academic world and which, for many years, was by far and away the main reference work for all studies in Galician linguistics.